Investigação sobre medo e ansiedade nas artes marciais - Pennacchioni, Pedro Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Fear can be characterized as an adverse emotional state, which triggers psychological malaise and physiological consequences such as dizziness, nausea, excessive sweating palpitations and shortness of breath, among others. Anxiety is closely related to fear, but is characterized as a disorder in which the causative agent of fear is not present and is thus anticipated. Understanding how these emotions affect the performance of martial artists and its development will contribute to improvement of these practitioners. In the early days of humanity such emotions were treated naturally because they were intrinsically related to man's everyday In current days we see a transformation in the martial arts. An art used exclusively for survival in the past, today takes a competitive and display character. This radical change throughout history takes the naturalness in dealing with such emotions from humankind. Investigating how such emotions develop can be the key to improving the performance of martial artists is in its competitive application or for self defense in violent society we're in today. Therefore, this study has the objective of investigating the influence of the emotions of fear and anxiety in the performance of martial artists and how these arts contributed to better manage these emotions. For this, a literature review of research was carried out, involving articles, reports, books, magazines and electronic platforms seeking to achieve the goals set. So we can conclude that there are several methods of preparation to deal with such emotions evident in the literature but the most effective are mainly based on taking into account the context and prepare the practitioner to adapt to different combat situations. After analyzing the material found and selected to make this work, we ... (Complete abstract electronic access below)

O medo pode ser caracterizado como um estado emocional adverso, que desencadeia mal-estar psicológico e reflexos fisiológicos como tontura, náuseas, suor excessivo palpitações e falta de ar, entre outros. A ansiedade está intimamente relacionada ao medo, porém se caracteriza por ser um transtorno onde o agente causador do medo não está presente e é assim antecipado. Compreender como essas emoções afetam o desempenho de artistas marciais e seus desdobramentos contribuirá para melhora desses praticantes. Nos primórdios da humanidade, tais emoções eram tratadas com naturalidade pois estavam intrinsecamente relacionadas com o cotidiano do homem primitivo. Nos dias de hoje observamos uma transformação nas artes marciais. Uma arte antes usada exclusivamente para a sobrevivência hoje toma um caráter competitivo e de exibição. Essa mudança radical ao longo da historia tira do homem a naturalidade em lidar com essas emoções. Investigar como se desdobram tais emoções pode ser a chave para melhorar o desempenho de artistas marciais seja em sua aplicação competitiva ou para autodefesa na sociedade violenta do mundo atual. Com isso, este estudo possui como objetivo investigar a influência das emoções de medo e ansiedade no desempenho de artistas marciais e a maneira como tais artes contribuíram para melhor manejar essas emoções. Para isso, foi realizada uma pesquisa de revisão bibliográfica, envolvendo artigos, reportagens, livros, revistas e plataformas eletrônicas buscando alcançar os objetivos traçados. Após a análise do material encontrado e selecionado para compor este trabalho, pudemos constatar que há diversos métodos de preparo para lidar com tais emoções evidenciados na literatura, contudo as estratégias mais efetivas se baseiam, principalmente, em levar em consideração ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Artes marciais; Medo; Ansiedade; Esportes - Aspectos psicológicos